New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records - Fachin, Diego Aguilar; Carvalho-Filho, Fernando Da Silva (Zootaxa, 2020)
Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae: Hermetiinae) has been known from only the male holotype collected in 1951 from the state of Bahia, Brazil, but currently lost or destroyed. No specimens have been reported over the last 60 years since its description. Here we bring together records of additional specimens of both sexes—one male and 28 females—from 13 localities in five Brazilian states, in addition to the type locality. A detailed redescription of the species is provided which includes the puparium, male and female terminalia, biological information, and a distribution map.